Prenatal androgen treatment impairs the suprachiasmatic nucleus arginine-vasopressin to kisspeptin neuron circuit in female mice - Jamieson, Bradley B.; Moore, Aleisha M.; Lohr, Dayanara B.; Thomas, Simone X.; Coolen, Lique M.; Lehman, Michael N.; Campbell, Rebecca E.; Piet, Richard (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is associated with elevated androgen and luteinizing hormone (LH) secretion and with oligo/anovulation. Evidence indicates that elevated androgens impair sex steroid hormone feedback regulation of pulsatile LH secretion. High androgens in PCOS may also disrupt the preovulatory LH surge. The mechanisms through which this might occur, however, are not fully understood. Kisspeptin (KISS1) neurons of the rostral periventricular area of the third ventricle (RP3V) convey hormonal cues to the gonadotropin-releasing hormone (GnRH) neurons. In rodents, the preovulatory surge is triggered by these hormonal cues and coincident timing signals from the central circadian clock in the suprachiasmatic nucleus (SCN). Timing signals are relayed to GnRH neurons, in part, via projections from SCN arginine-vasopressin (AVP) neurons to RP3VKISS1 neurons. Because rodent SCN cells express androgen receptors (AR), we hypothesized that these circuits are impaired by elevated androgens in a mouse model of PCOS. In prenatally androgen-treated (PNA) female mice, SCN Ar expression was significantly increased compared to that found in prenatally vehicle-treated mice. A similar trend was seen in the number of Avp-positive SCN cells expressing Ar. Anterograde tract-tracing revealed reduced SCNAVP neuron projections to the RP3V and a significantly lower proportion of RP3VKISS1 neurons with close appositions from SCNAVP fibers. Functional assessments showed, however, that RP3VKISS1 neuron responses to AVP were maintained in PNA mice despite apparent structural differences. These findings indicate that PNA changes some of the neural circuits that regulate the preovulatory surge. These impairments might contribute to ovulatory dysfunction in PNA mice modeling PCOS.